Pengembangan Video Interaktif Pembelajaran Nahwu “Belajar 10 Menitan” Berbasis TikTok untuk Siswa SMK - Novel, Novel; Mahliatussikah, Hanik (Aphorisme: Journal of Arabic Language, Literature, and Education, 2025)
This study aims to develop interactive Nahwu learning videos on TikTok that follow the “Learn in 10 Minutes” concept. This study uses the ADDIE Research and Development (R&D) model, which includes needs analysis, content design, video development, implementation via TikTok, and initial evaluation based on audience responses. The results of this study are 22 interactive videos with a maximum duration of 10 minutes, equipped with quizzes based on Nahwu material created with AI-based Canva. Initial responses indicate 120–411 viewers per video and 4–19 likes per video, despite the new content. The primary data subjects were 30 grade XII students from SMK al-Ikhwaniyah Jakarta, with open interviews via WhatsApp, and secondary data from a journal article. The researcher then conducted a thematic, descriptive, qualitative analysis that integrated the ADDIE stages. Based on the existing data, this study found that this teaching media is interesting, easy to understand, and relevant to the digital generation. Further research is needed to assess its effectiveness on learning outcomes empirically.